Expanding the Parameters of Participatory Public Law: A Democratic Right to Public Participation and the State’s Duty of Public Consultation - Liston, Mary (McGill Law Journal / Revue de droit de McGill, 2017)
This article examines the potential for an improved and expanded democratic relationship between the state and its legal subjects in public law. In Part I, I synthesize several of the compatible features of liberal, civic republican, and deliberative democratic theories in order to advance a new framework for public law in Canada that grounds a right to public participation, and the state’s public consultation duties. The framework illustrates how liberalism, civic republicanism and deliberative democracy possess mutually beneficial effects for public law. This type of democratically-informed common law juridical relationship has not yet been achieved—the topic of Part II—but, in Part III, I employ two typical Canadian public law cases to highlight the nature of current limitations as a springboard to suggest that expanded participation rights are both immanent and possible in Canada. In Part IV, I argue that along with the framework from Part I, jurisprudential pieces are already in place to expand the parameters of participatory public law. Drawing on insights from other jurisdictions, current limitations and anxieties about this expansion can be mitigated or overcome. I then briefly consider two criticisms concerning the effect that more robust public participation requirements may have on courts and governments. Drawing on the theoretical framework presented in Part I, I conclude that an individual right to public participation combined with a general duty of public consultation is an essential legal requirement in modern rights-respecting democracies, such as Canada’s, which aspire to be deliberative, fair, and participatory.